A new genus and species of Tetrastichinae (Hymenoptera: Eulophidae) inducing galls in seed capsules of Eucalyptus - Kim, Il-Kwon; la Salle, John (Zootaxa, 2008)
Leprosa milga Kim & La Salle gen. & sp. nov. (Hymenoptera: Eulophidae: Tetrastichinae) is described from Eucalyptus seed capsules. The new species is an Australian seed gall inducer which has become established in South Africa and Italy. The relationship of Leprosa to two other genera of seed gall inducing tetrastichines, Quadrastichodella and Moona, is discussed.